2013
DOI: 10.15230/scsk.2013.39.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Whitening Effects of Adamantyl Benzamide Derivatives

Abstract: The structure activity relationship of polyhydroxylated benzamide derivatives for whitening effects was examined. The adamantyl benzamide derivatives with catechol (3,4-dihydroxyphenyl) of B-ring part showed good anti-melanogenesis activity, but the inhibitory activity of mono-hydroxyphenyl (3-OH or 4-OH) or 3,4-dimethoxyphenyl substituted derivatives was decreased or lost. Therefore the catechol unit was appeared to be the crucial factor for the inhibition of melanogenesis. And the existence of 2-OH of A-ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our previous study, we synthesized various derivatives of N ‐benzylbenzamides as novel skin‐lightening agents and found that AP736 downregulates microphthalmia‐associated transcription factor (MITF) and tyrosinase by inhibiting the elevation in cAMP and activation of cAMP response element binding protein (CREB) and protein kinase A (PKA) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we synthesized various derivatives of N ‐benzylbenzamides as novel skin‐lightening agents and found that AP736 downregulates microphthalmia‐associated transcription factor (MITF) and tyrosinase by inhibiting the elevation in cAMP and activation of cAMP response element binding protein (CREB) and protein kinase A (PKA) …”
Section: Introductionmentioning
confidence: 99%
“…5,6 In our previous study, we synthesized various derivatives of N-benzylbenzamides as novel skin-lightening agents and found that AP736 downregulates microphthalmia-associated transcription factor (MITF) and tyrosinase by inhibiting the elevation in cAMP and activation of cAMP response element binding protein (CREB) and protein kinase A (PKA). [7][8][9] In this study, we conducted a clinical trial to compare the whitening effects of a topical formulation containing AP736 with that of a vehicle control formulation to verify the findings obtained using the in vitro model.…”
Section: Introductionmentioning
confidence: 99%